New data from old collections: Retouch-induced marks on Australian hardwood boomerangs. (June 2021) - Martellotta, Eva Francesca; Wilkins, Jayne; Brumm, Adam; Langley, Michelle C.
Highlights: Ethnographic evidence reveals the use of boomerangs as retouchers in Australia. Use-marks on boomerangs comparable with stigmata on Palaeolithic bone retouchers. First traceological evidence of multipurpose nature of Australian boomerangs. Abstract: Australian lithic assemblages contain a great number of retouched tools. Despite this fact, however, material evidence for, and studies, on the retouching tools utilised to create these technologies are limited, especially regarding their use in percussion retouch. Indirect evidence found in ethnographic literature suggests that wooden items – specifically boomerangs – were frequently utilised as retouchers. In this study, a sample of museum-curated boomerangs (n = 100) was analysed using a traceological approach developed for the study of bone retouchers in European contexts in order to determine if characteristic – retouched induced - traces were present. Retouch-induced marks were identified on 26% of the boomerangs examined and were comparable to those traces observed on the surfaces of ancient European bone retouchers. Our findings constitute the first traceological identification of hardwood boomerangs being used as retouchers in various Aboriginal Australian contexts and emphasise the need for a systematic study of this specific technological activity in this region.